The 'Red-Ink Grants': the Malays and the land - Mobarak Ali, Bashiran Begum; Mohamad, Nor Asiah (International Islamic University Malaysia, 2007)
British policy was to preserve and protect the Malay race on the assumption that they, despite being the majority, are historically a disadvantaged race. In addition, they were in need of economic protection against the more aggressive immigrants. Therefore, with the declaration of independence in 1957, a new written constitution was formulated for the Federation of Malaya with the inclusion of Malay special privileges. These privilages include the reservation of land, operation of quotas for licenses and and permits, scholarships, etc. This article seek to examine the foundation of Malay reservation land policies in Peninsular Malaysia in the last 50 years and the present policy of the government. It also discusses the challenges faced by the Malaysian government in escalating the develepmont of the Malay Reservation institution and to explain the strategies and policies adopted to meet these challenges.